2021
DOI: 10.3390/jpm11111238
|View full text |Cite
|
Sign up to set email alerts
|

Dismal Survival in COVID-19 Patients Requiring ECMO as Rescue Therapy after Corticosteroid Failure

Abstract: (1) Background: COVID-19 may lead to refractory hypoxemia requiring venovenous extracorporeal membrane oxygenation (ECMO). Survival rate if ECMO is implemented as rescue therapy after corticosteroid failure is unknown. We aimed to investigate if ECMO implemented after failure of the full-recommended 10-day corticosteroid course can improve outcome. (2) Methods: We conducted a three-center cohort study including consecutive dexamethasone-treated COVID-19 patients requiring ECMO between 03/2020 and 05/2021. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“… 35 , 36 , 37 , 38 , 39 Studies were judged to be at some risk of bias for confounding adjustment and for statistical analysis and reporting if they did not account for clinically important confounders using either logistic regression or Cox proportional hazards models. 15 , 39 , 44 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 Studies reporting adjusted analyses were judged to be at some risk of bias for statistical analysis 35 , 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 if they did not adhere to methodological standards set by the PROGRESS guidelines, 19 , 20 , 21 , 22 in particular with regards to a priori selection of clinically important confounders and consideration of an appropriate sample size to minimise potential overfitting. 28 , 76 The composition and methodological quality of individual prediction models for each study and funnel plots used to evaluate for publication bias among variables that were assessed in at least ten studies are included in the appendix (p 36–41 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the increase in mortality might stem from selection bias for patients with more severe ARDS refractory to adjunctive therapies than earlier on in the pandemic. Even amongst those who eventually require ECMO, a study of 40 patients found that mortality rates of patients receiving ECMO after a full 10-day course of dexamethasone was 100% compared to 57% where ECMO was instituted before completing the course of dexamethasone [ 69 ]. In addition to this, immunomodulatory treatment might be associated with increased rates of secondary infections, which itself is associated with increased mortality rates [ 70 ], though this is not confirmed by all the available evidence [ 71 ].…”
Section: Discussionmentioning
confidence: 99%